Modul Customer Service pada Aplikasi Komputerisasi Standar Akuntansi Perbankan berbasis Website - Ravita Nurul Asmi; Isram Rasal (Universitas Hamzanwadi, 2023)
Practicing students have difficulty in using standard banking accounting computerization applications because they still use disk operating systems and virtual machines. This happens because special knowledge is needed to run the application. This research aims to create a customer service module on a website-based standard banking accounting computerized application so that it can be used for learning operations in the ManLan Lab more easily. Programming using CodeIgniter and MySQL with a waterfall method approach in the system development life cycle, starting from the initial phase to the final phase of development. Data analysis using literature study and observation. This research involved 1 staff, 3 practicum students, and 2 assistants and programmers at the Advanced Management Laboratory as research subjects. The system design stage uses a navigation structure and four types of Unified Modeling Language (UML). Testing is done with black box testing to ensure there are no functional errors in the system. The results of our finding are in the form of a customer service module in the computerized application of banking accounting standards which is used as a depiction of customer service tasks in banks through an application system. And the results of black box testing show the system runs well as expected. Therefore, this application is suitable for operational learning practicum.